EFISIENSI PRODUKSI BUDIDAYA IKAN BANDENG (Chanos chanos) DI KOTA TARAKAN - Nurlela Machmudin; Anang Sulistyo; Yeni Purwati (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2019)
AbstractChanges in milkfish production from year to year that occur in Tarakan City are influenced by several factors in agriculture, one of which is the use of production factors by fish farmers. In 2017, aquaculture productivity in Tarakan City averaged 1.2 tons / ha / year, lower than the national productivity of 2 tons / ha / year. High and low production is influenced by the use of factors of production. Farmers must pay attention to the use of factors of production so that there are no advantages and disadvantages and also factors in farmers as managers so that efficient conditions are achieved. This study aims to 1) analyze the factors that affect milkfish production in Tarakan City; 2) analyzing the efficiency of milkfish production in Tarakan City. The sample in this study were farmers who cultivated milk fish in pond areas. The number of samples is 40 people selected using the simple random sampling method. Data analysis uses the Cobb Douglas stochastic frontier Production Function which is processed using the frontier 4.1 application. The results showed that the significant production factors on milkfish production were land area (X1) and labor (X5). Large areas are able to produce large quantities of production through reducing the death rate of the stocked seeds, increasing the space for fish, so that the metabolism runs optimally which has a positive impact on the